PENGARUH PEMBERIAN ZAT PENGATUR TUMBUH ALAMI TERHADAP PERTUMBUHAN STEK STEVIA (Stevia rebaudiana B.) - Natalia Lusianingsih Sumanto; Ardian Eleonard Purba (Bioscientist : Jurnal Ilmiah Biologi, 2019)
This study aims to determine the effect of the concentration of coconut water and onion extract on the growth of stevia plant cuttings. The research was conducted in Juli until November 2019 in trial garden of the Politeknik Wilmar Bisnis Indonesia. This research uses factorial randomized block design. The first factors are concentration of coconut water consisting of five levels is AK0 = control, AK1 = coconut water 25%, AK2 = coconut water 50%, AK3 = coconut water 75% and AK4 = coconut water 100%. The second factor was the treatment of onion extract consisting of five treatments namely BM0 = control, BM1 = concentration of onion extract 25%, BM2 = concentration of onion extract 50%, BM3 = concentration of onion extract 75% and BM4 = concentration of onion extract 100%. Observation of the percentage of live cuttings, stem height, number of leaves and root length was done at 2 MST, 3 MST and 4 MST. The highest percentage of cuttings found in plants treated with 100% coconut water and onion extract, the highest plant height was found in the treatment of 100% concentration of coconut water and onion extract (3 MST and 4 MST), the highest number of leaves found in the treatment 100% concentration of coconut water and shallot extract (3 MST) and the highest root length was found in the treatment of 100% concentration of coconut water and shallot extract (2 MST, 3 MST and 4 MST).